The Fenchel duality formula, The Ekeland variational principle, and Rockafellar's Theorem for maximal monotonicity of subdifferentials. (3rd October 2022) - Takahashi, Wataru; Takeuchi, Yukio
Abstract : In this paper, we first give two versions of the Fenchel duality formula and Brøndsted-Rockafellar's theorem. The versions are useful and the proofs are not so difficult. Next, we present a theorem in a Banach space to reconsider the Ekeland variational principle and Takahashi's nonconvex minimization theorem proved in a complete metric space. Finally, using the version of the Fenchel duality formula, the Ekeland variational principle and the version of Brøndsted-Rockafellar's theorem, we prove a minimization theorem in a Banach space and then present a short proof of well–known Rockafellar's theorem for maximal monotonicity of subdifferentials.